Peran Microsoft Excel dalam Penyusunan Daftar Arsip Sekolah untuk Memudahkan Proses Temu Kembali Arsip - Rashwantika, Galuh; Athaya Nurul Fakhirah; Hasma Fazira Aghni; Fatkhur Rochman (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to analyze the role of Microsoft Excel in compiling school archive lists to facilitate the archive retrieval process and support the effectiveness of educational administration services. Archive management in schools is still largely done manually, creating obstacles in the process of searching and managing archive information. Therefore, it is necessary to utilize simple technology that can help improve the work efficiency of school administrative staff. This study uses a qualitative approach with a literature study method supported by a Microsoft Excel-based school archive data simulation. Data were collected through a literature review of relevant journals, books, and previous research, then analyzed using content analysis techniques to obtain an overview of the use of Microsoft Excel in school archive management. The results show that Microsoft Excel is able to produce a more structured archive list system through table, sort, filter, and data grouping features, thereby accelerating the archive retrieval process. In addition, the use of a simple dashboard in Excel helps administrative staff monitor archive conditions more effectively. These findings indicate that Microsoft Excel plays a role as a simple, economical and easy-to-implement digitalization solution in school archive management. The success of the archive retrieval system is greatly influenced by the consistency of data input and the accuracy of archive classification. Thus, Microsoft Excel can be an initial alternative for digitizing educational administration to improve the effectiveness of archives management services in schools.